Multifunctional sensor module with wireless transmission [electronic resource] - Chan, Kok Seng, 1992- , author; Lim, Cheng Siong, supervisor (2015)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2015